Pengaruh Kepemimpinan Terhadap Efektivitas Pengembangan Usaha Mikro Di Desa Katapang Kabupaten Bandung - Farid Arifin; Yogi Gumilar Saeful Akbar; Novan Ahmad Hanafi (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2024)
Microenterprises are vital to local economies, especially in developing countries, contributing greatly to job creation and economic growth. However, many of these enterprises face challenges such as limited resources and market access. Effective leadership plays a key role in determining the success of microenterprises by managing resources, motivating teams, and supporting innovation. Various leadership styles, such as transformational, transactional, and laissez-faire, influence the effectiveness of microenterprise development in different ways; transformational and transactional leadership generally favor growth, while laissez-faire style can decrease motivation and performance. In this study, the method used is a quantitative descriptive method with data analysis using Simple linear regression with testing on samples in Katapang Village based on primary data obtained from questionnaires distributed by researchers. This simple linear regression test analysis is supported by Validity Test, Reliability Test, Determination and Correlation Coefficient Test, as well as partial significance and joint significance. In addition, the targeted output in this study is to be used as publication material in accredited national journals, so that it can have an impact and be used as a reference for more stakeholders throughout Indonesia, especially in Bandung Regency which is the object of this research.